A new 28Si single crystal: counting the atoms for the new kilogram definition. (10th August 2017) - Bartl, G; Becker, P; Beckhoff, B; Bettin, H; Beyer, E; Borys, M; Busch, I; Cibik, L; D'Agostino, G; Darlatt, E; Di Luzio, M; Fujii, K; et al.
Abstract: A new single crystal from isotopically enriched silicon was used to determine the Avogadro constant N A by the x-ray-crystal density method. The new crystal, named Si28-23Pr11, has a higher enrichment than the former 'AVO28' crystal allowing a smaller uncertainty of the molar mass determination. Again, two 1 kg spheres were manufactured from this crystal. The crystal and the spheres were measured with improved and new methods. One sphere, Si28kg01a, was measured at NMIJ and PTB with very consistent results. The other sphere, Si28kg01b, was measured only at PTB and yielded nearly the same Avogadro constant value. The mean result for both 1 kg spheres is N A   =  6.022 140 526(70)  ×  10 23 mol −1 with a relative standard uncertainty of 1.2  ×  10 −8 . This value deviates from the Avogadro value published in 2015 for the AVO28 crystal by about 3.9(2.1)  ×  10 −8 . Possible reasons for this difference are discussed and additional measurements are proposed.